A simple label-free aptamer-based method for C-reactive protein detection. Issue 21 (16th May 2016) - Wu, Bin; Chen, Nandi; Wang, Qing; Yang, Xiaohai; Wang, Kemin; Li, Wenshan; Li, Qing; Liu, Wenjing; Fang, Hongmei
Abstract : We developed a simple label-free aptamer-based method for C-reactive protein (CRP) detection. Abstract : We developed a simple label-free aptamer-based method for C-reactive protein (CRP) detection. In our previous work, we obtained a G-rich aptamer named 6th-62-40, which exhibited good affinity and specificity toward CRP. Herein, we demonstrated that 6th-62-40 could enhance the fluorescence of thioflavin T (ThT). In the absence of CRP, ThT bound to the G-rich aptamer and formed an aptamer/ThT complex, which showed high fluorescence. However, the fluorescence decreased due to the formation of an aptamer/CRP complex in the presence of CRP. The proposed method was a rapid strategy for CRP detection with a detection limit of 380 pM.